Combined Effect of MTHFR C677T and PAI-1 4G/5G Polymorphisms on the Risk of Venous Thromboembolism in Chinese Lung Cancer Patients. (29th July 2021) - Wang, Baoyan; Xu, Peijuan; Shu, Qing; Yan, Simin; Xu, Hang
Venous thromboembolism (VTE) is a common and potentially fatal complication in cancer patients. Although several genetic risk factors related to thrombophilia have been identified, their contributions for the occurrence of VTE in cancer patients have conflicting results. The aim of this study was to evaluated the gene polymorphisms of methylenetetrahydrofolate reductase (MTHFR) C677T and plasminogen activator inhibitor-1 (PAI-1) 4G/5G in lung cancer patients, with and without VTE, and the combined effect on the risk of VTE. 92 lung cancer patients diagnosed with VTE (VTE group) and 122 lung cancer patients without VTE (non-VTE group) were enrolled in the study. The gene polymorphisms were analyzed by the method of polymerase chain reaction-restriction fragment length polymorphism. Gene mutation of factor V Leiden was not detected both in non-VTE group and VTE group. The frequency of MTHFR C677T homozygous mutation in VTE group was 25.00%, higher than that in the non-VTE group without statistical difference. It was found that the PAI-1 4G4G genotype is associated with a higher risk of VTE (OR: 2.62, 95%CI: 1.19-5.75). Interestingly, the interaction between MTHFR C677T and PAI-1 4G/5G polymorphisms showed that the coexistence of the 2 homozygous mutation could further increase the risk of VTE. In conclusion, PAI-1 4G/5G polymorphism may be an increased risk factor for VTE among lung cancer patients in Chinese population. The homozygous MTHFR C677T mutation may be not a risk factor for VTE but increases the risk, accompanied with PAI-1 4G5G genotype.